The Clinical Effects of Aromatherapy Massage on Reducing Pain for the Cancer Patients: Meta-Analysis of Randomized Controlled Trials. (14th January 2016) - Chen, Ting-Hao; Tung, Tao-Hsin; Chen, Pei-Shih; Wang, Shu-Hui; Chao, Chuang-Min; Hsiung, Nan-Hsing; Chi, Ching-Chi
Abstract : Purpose . Aromatherapy massage is an alternative treatment in reducing the pain of the cancer patients. This study was to investigate whether aromatherapy massage could improve the pain of the cancer patients. Methods . We searched PubMed and Cochrane Library for relevant randomized controlled trials without language limitations between 1 January 1990 and 31 July 2015 with a priori defined inclusion and exclusion criteria. The search terms included aromatherapy, essential oil, pain, ache, cancer, tumor, and carcinoma. There were 7 studies which met the selection criteria and 3 studies were eventually included among 63 eligible publications. Results . This meta-analysis included three randomized controlled trials with a total of 278 participants (135 participants in the massage with essential oil group and 143 participants in the control (usual care) group). Compared with the control group, the massage with essential oil group had nonsignificant effect on reducing the pain (standardized mean difference = 0.01; 95% CI[ - 0.23, 0.24 ] ). Conclusion . Aromatherapy massage does not appear to reduce pain of the cancer patients. Further rigorous studies should be conducted with more objective measures.